2016
DOI: 10.1074/jbc.m116.730366
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of Mot1, a TATA-binding Protein (TBP)-DNA Dissociating Enzyme

Abstract: The essential Saccharomyces cerevisiae ATPase Mot1 globally regulates transcription by impacting the genomic distribution and activity of the TATA-binding protein (TBP). In vitro, Mot1 forms a ternary complex with TBP and DNA and can use ATP hydrolysis to dissociate the TBP-DNA complex. Prior work suggested an interaction between the ATPase domain and a functionally important segment of DNA flanking the TATA sequence. However, how ATP hydrolysis facilitates removal of TBP from DNA is not well understood, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 68 publications
4
8
0
Order By: Relevance
“…Genome-wide localization has also shown that Mot1 is predominately localized to promoters of genes it represses and activates, suggesting that Mot1 has a direct role in both types of regulation. This localization coincides with TBP localization at the promoters, and Mot1 has been shown to approach TBP from the upstream DNA, which is consistent with studies showing that the upstream DNA is required for Mot1 function and the results from Chapter II (Darst et al 2001, Wollmann et al 2011, Zentner and Henikoff 2013, Viswanathan et al 2016.…”
Section: Mot1 Regulates Initiation and Elongationsupporting
confidence: 74%
See 3 more Smart Citations
“…Genome-wide localization has also shown that Mot1 is predominately localized to promoters of genes it represses and activates, suggesting that Mot1 has a direct role in both types of regulation. This localization coincides with TBP localization at the promoters, and Mot1 has been shown to approach TBP from the upstream DNA, which is consistent with studies showing that the upstream DNA is required for Mot1 function and the results from Chapter II (Darst et al 2001, Wollmann et al 2011, Zentner and Henikoff 2013, Viswanathan et al 2016.…”
Section: Mot1 Regulates Initiation and Elongationsupporting
confidence: 74%
“…As already stated, the remaining sequence was exactly the same as the 5' Bio duplex. We then repeated the experiment to determine if TBP or (Maruta et al 1993, Viswanathan 2013, Viswanathan et al 2016). We determined if there was any change in the ATPase conformation between binding of ATP (as mimicked by the ground state ADP-BeF 3 ) and hydrolysis (as mimicked by the transition state ADP-AlF 4 ) (Fisher et al 1995, Liu et al 2008.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, Mot1 overexpression inhibits cell growth due to enhanced and unbalanced activity toward TBP (14,43). Consistent with this, recent evidence has suggested that Mot1 does not efficiently dissociate high affinity TBP–DNA complexes (44) and, in addition, Mot1 has been implicated in the turnover of nonspecific or transcriptionally inactive interactions with DNA (45).…”
Section: Introductionmentioning
confidence: 63%